Utilization of Pineapple as Essential Oil for Respiratory Disorders: Case Study - Permana, Roni; Afiyatusyifa, Fidya; Dewi, Riska Yuliana (TIME in Physics, 2025)
This study aims to examine the effectiveness of pineapple (Ananas comosus) Essential oil in alleviating mild respiratory disorders such as cough and shortness of breath. A quasi-experimental method was used, involving two groups: an experimental group receiving therapy with pineapple Essential oil and a control group receiving warm water without oil. The results showed a significant reduction in respiratory symptoms in the experimental group (p < 0.01), while no significant change was observed in the control group. The bromelain content and volatile compounds in pineapple play a role in reducing inflammation and helping to open the airways. These findings indicate that pineapple Essential oil has potential as a natural alternative therapy for mild respiratory problems.